Penerapan Fisioterapi Dada (Clapping) untuk Mengatasi Bersihan Jalan Napas Tidak Efektif pada Anak dengan Bronkopneumonia - Ade Andriyana; Vincencius Surani; Srimiyati Srimiyati (Lembaga Pengembangan Kinerja Dosen, 2026)
Bronchopneumonia is a type of infection of the lower respiratory tract that often occurs in children, especially toddlers. This disease is characterized by inflammation of the bronchioles and lung tissue which triggers increased production of secretions in the airways. The buildup of secretions often causes nursing problems in the form of ineffective airway clearance, which is indicated by ineffective coughing, rapid breathing, shortness of breath, and the appearance of additional breath sounds such as rales. Chest physiotherapy in children was carried out to evaluate the effectiveness of the clapping technique in helping to clear the airway in bronchopneumonia patients. The method applied in evidence-based practice (EBP) uses case studies with a nursing care approach. Intervention was given to three patients with a diagnosis of bronchopneumonia for three days, with a duration of approximately 1-2 minutes in each area of ​​the chest. Evaluation is carried out using a stethoscope and measuring time (clock), with the results recorded on an observation sheet. After chest physiotherapy (clapping), the three patients showed improvement in airway clearance, which was indicated by respiratory frequency returning to normal, no additional breath sounds (ronchi), and reduced secretion production. Based on these results, it can be concluded that the application of EBP through chest physiotherapy is effective in increasing airway clearance in bronchopneumonia patients.